A New Concept of a Porous Carbon Interlayer Impregnated with Sulfur for Long‐Life and High‐Energy LiS Batteries - Park, Jong Won; Kang, Jin Kyeong; Koh, Jeong Yoon; Kim, Seok; Jung, Yongju (Bulletin of the Korean Chemical Society, 2019)
We present a new interlayer concept for the realization of high‐energy‐density LiS batteries. Disordered mesoporous carbons replicated by silica nanoparticles were partially filled with sulfur via a melt‐diffusion method. Sulfur‐impregnated disordered mesoporous carbon (DMC‐S) composites were used as an interlayer between a cathode and anode to provide additional active materials for a LiS cell. The LiS cell with the DMC‐S interlayer exhibited an approximately two‐fold increase in areal capacity compared with the control cell without an interlayer. DMC‐S composites offer the unique advantage of acting as a porous framework to accommodate active materials and suppress polysulfide diffusion. We propose that this new approach provides a viable path for the development of LiS batteries with a high‐energy density and excellent cycling stability.